Work-Related Stress Among Chefs: A Predictive Model of Health Complaints - Antonio Cerasa; Antonio Cerasa; Carmelo Fabbricatore; Giuseppe Ferraro; Rocco Pozzulo; Iolanda Martino; Marco Tullio Liuzza (Frontiers Media S.A., 2020)
Aim: We studied occupational stress and its effects on health in a sample of Italian chefs using a structural equation modeling (SEM) analytical approach.Methods: In an online study, 710 chefs were recruited through the Italian Chefs Federation. They answered several questionnaires to evaluate whether the risk of occupational stress (measured with the Karasek's Job Content Questionnaire and Siegrist's Effort-Reward Imbalance) correlates with the quality of life and the prevalence of health complaints. We also sought to evaluate whether individual characteristics (age, sex or body mass index) or work-related factors (i.e., chef categories, job duration, and length of working day) might be considered as stress risk factors.Results: Forty-seven percent of the chefs [88% male, mean age: 44.4 ± 6.3 years; body mass index (kg/m2): 28.5 ± 1.2; job duration: 24.9 ± 4.1 years; working hours per week: 66.4 ± 28.9] reported, at least, two or more health complaints (i.e., gastrointestinal, blood pressure, and musculoskeletal problems). SEM analyses demonstrated that occupational job duration and the length of working week in chefs are significantly associated with a lower quality of life and an increasing prevalence of health complaints. This relationship is mediated by the presence of high level of occupational stress, which was revealed with a prevalence ranging from 13.8 to 24.9%. Age, sex, and unhealthy lifestyles do not affect this pattern of findings.Conclusion: Job duration and the length of working day can be considered as stress predictors in chef-related daily activity, which increase the likelihood of illness.